2(z-3)+4(2z-7)=

Simple and best practice solution for 2(z-3)+4(2z-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(z-3)+4(2z-7)= equation:


Simplifying
2(z + -3) + 4(2z + -7) = 0

Reorder the terms:
2(-3 + z) + 4(2z + -7) = 0
(-3 * 2 + z * 2) + 4(2z + -7) = 0
(-6 + 2z) + 4(2z + -7) = 0

Reorder the terms:
-6 + 2z + 4(-7 + 2z) = 0
-6 + 2z + (-7 * 4 + 2z * 4) = 0
-6 + 2z + (-28 + 8z) = 0

Reorder the terms:
-6 + -28 + 2z + 8z = 0

Combine like terms: -6 + -28 = -34
-34 + 2z + 8z = 0

Combine like terms: 2z + 8z = 10z
-34 + 10z = 0

Solving
-34 + 10z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '34' to each side of the equation.
-34 + 34 + 10z = 0 + 34

Combine like terms: -34 + 34 = 0
0 + 10z = 0 + 34
10z = 0 + 34

Combine like terms: 0 + 34 = 34
10z = 34

Divide each side by '10'.
z = 3.4

Simplifying
z = 3.4

See similar equations:

| 9w-17w=-16 | | 48y^2+120y+75=0 | | -65-(+42)= | | 5b+2b-6=15 | | (2x-1)(8-x)=0 | | 2x-8x-44=100 | | 5(3z-1)-2(z+1)=10(z+1) | | 2a-3a=7-6a+4-11 | | 14x^3-38x^2+44x-15=0 | | x-9=87 | | friends+fake= | | 15n=-15 | | X+38+38=90 | | -73+2x+7x=98 | | 4(u+3)-3(3u-7)= | | 3(x-2)(x-2)+3=6x-12 | | -8(t-5)-(t+3)=10 | | p+7=7-6p | | X+45+35.8=90 | | 5/8c-8=2 | | 92+78=180 | | Y=300x^2-12 | | -41-5x+7x=19 | | (r-4)(r+1)+(r-4)(r+6)= | | 25x-30=-5 | | -x^2-24+45=0 | | X+16.5=90 | | 1.6(2x-1)=2(.4x+.7) | | 12=8n-(2n-3) | | -2y=-6-7x | | -2x-120+12x=40 | | lgx^3+2lgx^2-14=0 |

Equations solver categories